A Statistical Formulation for Master Modulus Curves of a Vinyl Ester Polymer. Issue 10 (3rd July 2018) - Sullivan, Rani W.; Simsiriwong, Jutima
ABSTRACT: Master modulus curves are developed for a vinyl ester polymer with variability in its material properties. Tensile creep strains were obtained at three temperatures below the T g through digital image correlation. A spectrum function was used to represent the viscoelastic strain response and modulus. A two-parameter Weibull distribution was used to characterize the probability distribution of the longitudinal modulus. The Weibull probability density functions of the viscoelastic modulus were obtained for each test configuration and found to be time and temperature dependent. Longitudinal modulus curves at constant probabilities were used to develop the master curves using the time–temperature superposition principle. GRAPHICAL ABSTRACT: